Adhesion of Platelets to Collagen Devoid of Telopeptides - Wojtecka-Lukasik, Elzbieta; Sopata, Irena; Wize, Janina; Skonieczna, Maria; Niedzwiecka-Namysłowska, Izabella; Kowalski, E (Thrombosis and Haemostasis, 1967)
Collagen devoid of telopeptides has been prepared according to the method of Rubin. It has been shown that this partially degraded collagen has not lost the ability to adhere and to aggregate platelets.